2023
DOI: 10.1055/a-2131-7180
|View full text |Cite
|
Sign up to set email alerts
|

Global prospective case series of ERCPs using a single-use duodenoscope

Abstract: BACKGROUND & AIMS The first commercialized single-use duodenoscope was cleared by the US Food and Drug Administration in December 2019. Data regarding endoscopic retrograde cholangiopancreatography (ERCP) using a single-use duodenoscope are needed on a broader range of cases conducted by endoscopists with varying levels of experience in a wide range of geographic areas. METHODS Sixty-one endoscopists at 22 academic centers in 11 countries performed ERCP procedures in adult patients aged 18 and older. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The largest cohort studying ERCP-related adverse events with SDs showed an overall infection rate of 1.63% [25], which is similar to the classic analysis by Andriulli et al with 16,855 patients (1.44%) [26]. The comparable infection rate also shows that endogenous infection can still occur with the use of a SD, so the procedure-related infection rate is not guaranteed to be lower than the rate for reusable duodenoscopes [25].…”
Section: Accepted Manuscriptsupporting
confidence: 65%
“…The largest cohort studying ERCP-related adverse events with SDs showed an overall infection rate of 1.63% [25], which is similar to the classic analysis by Andriulli et al with 16,855 patients (1.44%) [26]. The comparable infection rate also shows that endogenous infection can still occur with the use of a SD, so the procedure-related infection rate is not guaranteed to be lower than the rate for reusable duodenoscopes [25].…”
Section: Accepted Manuscriptsupporting
confidence: 65%
“…Multiple studies have confirmed that SUDs are associated with high cannulation rates, technical performance, and safety profile (Table 2). 26,28 20–25,27 A recent systematic review and meta‐analysis analyzed the technical performance and safety of ERCPs using SUDs 28 . The pooled rate of successful cannulation was 95% and sphincterotomy could be successfully performed in all cases.…”
Section: Single‐use Duodenoscopes and Endoscopesmentioning
confidence: 99%
“…In this issue of Endoscopy, Bruno et al [9] present the results of the largest multicentric international case series on the use of single-use duodenoscopes for endoscopic retrograde cholangiopancreatography (ERCP) procedures. The study was conducted between 2019 and 2022 and included a total of 551 procedures, performed by 61 endoscopists at 22 academic centers from 11 different countries.…”
mentioning
confidence: 99%